DIAGNOSTICO DE LA LEPRA POR BACTERIOSCOPIA LINFATICA - VALDES ORNELAS, OSCAR (Instituto de Salubridad y Enfermedades Tropicales, CD MEXICO, DF, MEX, 1948)
Descr of the boundaries and physical characteristics of the Valley of Mexico precede notes upon a few spp from the area: Ambystoma lacustris, Rana montezumae, Rhyacosiredon altamirani, R zempoalensis, Siredon mexicanum and Bufo com-pactilis A number o
AN ESC NAC CIENC BIOL
Keywords: DIAGNOSTICO, LEPRA, BACTERIOSCOPIA, LINFATICA; CIENCIAS DE LA VIDA; FISIOLOGIA HUMANA; FISIOLOGIA MEDICA